Relations between self-reported daily-life fatigue, hearing status, and pupil dilation during a speech perception in noise task - Wang, Yang; Naylor, Graham; Kramer, Sophia E.; Zekveld, Adriana A.; Wendt, Dorothea; Ohlenforst, Barbara; Lunner, Thomas (Lippincott, Williams & Wilkins, 2018)
Objective: People with hearing impairment are likely to experience higher levels of fatigue because of effortful listening in daily communication. This hearing-related fatigue might not only constrain their work performance but also result in withdrawal from major social roles. Therefore, it is important to understand the relationships between fatigue, listening effort, and hearing impairment by examining the evidence from both subjective and objective measurements. The aim of the present study was to investigate these relationships by assessing subjectively measured daily-life fatigue (self-report questionnaires) and objectively measured listening effort (pupillometry) in both normally hearing and hearing-impaired participants. Design: Twenty-seven normally hearing and 19 age-matched participants with hearing impairment were included in this study. Two self-report fatigue questionnaires Need For Recovery and Checklist Individual Strength were given to the participants before the test session to evaluate the subjectively measured daily fatigue. Participants were asked to perform a speech reception threshold test with single-talker masker targeting a 50% correct response criterion. The pupil diameter was recorded during the speech processing, and we used peak pupil dilation (PPD) as the main outcome measure of the pupillometry. Results: No correlation was found between subjectively measured fatigue and hearing acuity, nor was a group difference found between the normally hearing and the hearing-impaired participants on the fatigue scores. A significant negative correlation was found between self-reported fatigue and PPD. A similar correlation was also found between Speech Intelligibility Index required for 50% correct and PPD. Multiple regression analysis showed that factors representing “hearing acuity” and “self-reported fatigue” had equal and independent associations with the PPD during the speech in noise test. Less fatigue and better hearing acuity were associated with a larger pupil dilation. Conclusions: To the best of our knowledge, this is the first study to investigate the relationship between a subjective measure of daily-life fatigue and an objective measure of pupil dilation, as an indicator of listening effort. These findings help to provide an empirical link between pupil responses, as observed in the laboratory, and daily-life fatigue.